2017
DOI: 10.1142/s0217732317400119
|View full text |Cite
|
Sign up to set email alerts
|

A new approach for manufacturing and processing targets to produce 99mTc with cyclotrons

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…All samples passed all of the tests successfully. The cladding remained on the substrate until a chemical dissolution was used to remove it as is done regularly in target processing [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples passed all of the tests successfully. The cladding remained on the substrate until a chemical dissolution was used to remove it as is done regularly in target processing [11].…”
Section: Resultsmentioning
confidence: 99%
“…Only target cladding is discussed as other stages of processing, dissolution, separation, and recovery are no different than when using other cladding techniques [11].…”
mentioning
confidence: 99%
“…Methods proposed for large-scale target manufacturing include: electrophoretic deposition [19], pressing and sintering [11], electroplating, and carburization. Plasma spraying was investigated, but customized equipment to reduce wasteful overspray became too costly for the process to be feasible [21]. Regardless of manufacturing procedure, targets must dissipate heat during irradiation, and higher thermally conductive substrates allow higher power proton beam lines, which yield more 99m Tc.…”
Section: Competitive Target Designsmentioning
confidence: 99%
“…shown that during irradiation with 6 kW, water cooling at a rate of 8 L/min will maintain the molybdenum below 260°C, which is the temperature at which any oxides inadvertently generated in situ could volatilize and contaminate the target holder and cyclotron [21]. The elliptical shape reduces the heat flux associated with high current sources because of its increased area compared with a circular target.…”
Section: Design Rationalementioning
confidence: 99%
See 1 more Smart Citation